H53 Does the risperidone influence weight in huntington's disease?. (September 2018) - Konvalinkova, Romana; Dusek, Pavel; Doleckova, Kristyna; Uhrova, Tereza; Roth, Jan; Klempir, Jiri
Abstract : Unintended weight loss is a negative prognostic factor in Huntington's disease (HD). Exact mechanism of weight loss and influence of therapeutic intervention on this symptom is still unclear. In Prague centre Registry database containing 309 examinations of patients (age 50.3±13.4 years, disease duration 9.13±3.51 years, number of CAG repeats from 40 to 70) were analysed. Correlation analysis was performed between body mass index (BMI) and Unified Huntington's Disease Rating Scale – motor subscores (voluntary, oculomotor, chorea, dystonia, rigidity) and functional scales were used. None of the Pearson's correlation were significant. Our results may indicate that BMI may be independent parameter in this particular stage of the disease course. Of the database, 154 examinations were on risperidone and 155 were without risperidone therapy. Age, CAG repeats and disease duration did not differ between the two groups (p=0.1, p=0.9, p=0.26 respectively). Patients on risperidone therapy had significantly higher weight (Mann-Whitney U-test, p<0.0001). Additionally, we performed a linear model using ordinary least squares calculation to count for the effect of disease progression and motor subscores. The effect of risperidone was independent on the disease progression (i.e. disease duration, CAG expansion, age) and voluntary and involuntary movements. In subsequent analysis, 49 events on tiapride therapy and 260 events off tiapride therapy were compared, weight in those two groups did not differ. A longitudinal study must be performed to prove the causality of risperidone effect on weight in HD.